Associations between hypo-HDL cholesterolemia and cardiometabolic risk factors in middle-aged men and women: Independence of habitual alcohol drinking, smoking and regular exercise. Issue 3 (May 2017) - Wakabayashi, Ichiro; Daimon, Takashi
Abstract: Objective: Hypo-HDL cholesterolemia is a potent cardiovascular risk factor, and HDL cholesterol level is influenced by lifestyles including alcohol drinking, smoking and regular exercise. The aim of this study was to clarify the relationships between hypo-HDL cholesterolemia and cardiovascular risk factors and to determine whether or not these relationships depend on the above-mentioned lifestyles. Methods: The subjects were 3456 men and 2510 women (35–60 years of age) showing low HDL cholesterol levels (<40 mg/dl for men and <50 mg/dl for women) and their age-matched control subjects showing normal HDL cholesterol levels. Each cardiometabolic risk factor was compared between the groups with and without hypo-HDL cholesterolemia. Data for hypo-HDL cholesterolemic subjects not having habits of alcohol drinking, smoking and regular exercise (men, n  = 333; women, n  = 1410) and their age-matched control subjects were also analysed. Results: Both in men and in women of overall subjects and subjects without histories of alcohol drinking, smoking and regular exercise, odds ratios of subjects with hypo-HDL cholesterolemia vs. subjects with normo-HDL cholesterolemia for high body mass index, high waist-to-height ratio, high triglycerides, high lipid accumulation product and multiple risk factors (three or more out of obesity, hypertension, dyslipidaemia and diabetes) were significantly higher than the reference level of 1.00. These associations in overall subjects were found when the above habits were adjusted. Conclusions: Hypo-HDL cholesterolemic men and women have adverse cardiovascular profiles, such as obesity, hypertriglyceridemia and multiple risk factors, independently of age, alcohol drinking, smoking and regular exercise.